Numerical and experimental investigation on multi-zone chemical mechanical planarization - Wang, Tongqing; Lu, Xinchun (Microelectronic engineering, 2011)
The contact stress distribution on the wafer surface and material removal rate profile of the wafer for different applied load at zone 1 in the 12-inch and four-zone CMP. In this paper, the contact stress distribution on the wafer surface in multi-zone CMP is investigated using finite-element analysis based on a 12-in. and four-zone CMP model. Afterwards, a 12-in. and four-zone polishing head with the same size as the numerical model is developed and CMP experiments are carried out to verify the above numerical calculations. The results show that both the contact stress on the wafer surface and the material removal rate of the wafer can be adjusted by varying the applied load at the zones and the retaining ring in multi-zone CMP, the multi-zone MRR model appears to agree well with the experimental data, and the non-uniformity material removal rate of the wafer can be improved in multi-zone CMP. It is expected that this investigation can give some direct assistance to the 12-in. wafer fab.